Ecological change alters the evolutionary response to harvest in a freshwater fish. Issue 8 (4th October 2018) - Gobin, Jenilee; Lester, Nigel P.; Fox, Michael G.; Dunlop, Erin S.
Abstract: Harvesting can induce rapid evolution in animal populations, yet the role of ecological change in buffering or enhancing that response is poorly understood. Here, we developed an eco‐genetic model to examine how ecological changes brought about by two notorious invasive species, zebra and quagga mussels, influence harvest‐induced evolution and resilience in a freshwater fish. Our study focused on lake whitefish ( Coregonus clupeaformis ) in the Laurentian Great Lakes, where the species supports valuable commercial and subsistence fisheries, and where the invasion of dreissenid (zebra and quagga) mussels caused drastic shifts in ecosystem productivity. Using our model system, we predicted faster rates of evolution of maturation reaction norms in lake whitefish under pre‐invasion ecosystem conditions when growth and recruitment of young to the population were high. Slower growth rates that occurred under post‐invasion conditions delayed when fish became vulnerable to the fishery, thus decreasing selection pressure and lessening the evolutionary response to harvest. Fishing with gill nets and traps nets generally selected for early maturation at small sizes, except when fishing at low levels with small mesh gill nets under pre‐invasion conditions; in this latter case, evolution of delayed maturation was predicted. Overall, the invasion of dreissenid mussels lessened the evolutionary response to harvest, while also reducing the productivity and commercial yield potential of the stock. These results demonstrate how ecological conditions shape evolutionary outcomes and how invasive species can have a direct effect on evolutionary responses to harvest and sustainability.